Adapt to a harsher world: Memo to the high representative for foreign and security policy - Alicia García Herrero; Heather Grabbe; Jean Pisani-Ferry (Bruegel, 2024)
The job of High Representative for Foreign and Security Policy and Vice-President of the European Commission (HRVP) was designed for a different world than the one the European Union now grapples with: a world built on principles and governed by law, in which the EU was a force of attraction because of its mass, prosperity and good governance. Today's EU is weaker. It faces Russian aggression on its borders and a conflict in the Middle East where it has little influence. Economic security has become a much bigger priority. Whoever is elected as the next US president will continue the rivalry with China, and be more absorbed with the Indo-Pacific than with Europe. In the EU, China is widely acknowledged to be a rival, and even a threat. Yet it remains an essential trade partner and has also become a formidable economic competitor. The HRVP's role is constrained by a confusing and contested institutional structure, with prominent roles for the President of the Commission and President of the European Council in EU external representation. At the same time, the EU's external policy is more important than ever. A stark choice must be made on how to adapt the HRVP role to a world dominated by intimidation and brute force. There are two possible options. The first and best option is for the European Council to give the HRVP a stronger mandate to act on matters on which member states have decided to take common action. This would require stronger legal and financial capabilities to coordinate relevant policies in the EU institutions. In this model, the HRVP would be 'first among equals', both among the foreign ministers and among all commissioners with portfolios that touch on EU external relations. A second option would be to accept that the authority of the HRVP is more circumscribed than envisaged by the Lisbon Treaty, but to clarify the functions that the HRVP will keep. This requires a clear division of labour with other commissioners whose portfolios have an external dimension and implies forsaking responsibility for trade policy, development, enlargement and neighbourhood, and even defence procurement. We believe the first model is preferable. But most important is that the EU makes a choice and breaks the bad habit of nominally assigning powers to the HRVP while depriving her of the ability to exercise them in practice. Disempowering the HRVP's position would make the system even more dysfunctional.
Keywords: 330